2020
DOI: 10.1177/1558866120917176
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Examination of International Graduate Students’ Experiences With Campus Recreation Services

Abstract: International college students have become an important subgroup in U.S. higher education. However, their campus recreation participation rate is relatively low. Previous studies indicate significant factors preventing international students from campus recreation participation were lack of time, lack of workout partners, and lack of recreation information. Relatively little research has been undertaken on understanding and explaining campus recreation experiences among the international graduate student popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Studies also explored the motivational factors of participation such as socialization/peer support, competency/mastery (e.g., Anderson & Ramos, 2018; Beggs et al, 2014; Carter-Francique, 2011; Deng et al, 2021; Ramos et al, 2018), appearance (e.g., Cooper et al, 2012; Diehl et al, 2018), goal achievement (e.g., Lower-Hoppe et al, 2021; Snyder et al, 2017), entertainment/stimulation (e.g., Munusturalar et al, 2015; Shapiro et al, 2020). A few studies also investigated communication and marketing practices like information dissemination (e.g., Lee et al, 2020), the use of social media (e.g., Achen, 2015), the internet and word of mouth (e.g., Bilos & Galic, 2016), promotional items (e.g., Ciuffo et al, 2014), advertising and branding (e.g., Mills & Williams, 2016), and the campus recreation facility as an institutional recruitment tool (e.g., Weaver et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also explored the motivational factors of participation such as socialization/peer support, competency/mastery (e.g., Anderson & Ramos, 2018; Beggs et al, 2014; Carter-Francique, 2011; Deng et al, 2021; Ramos et al, 2018), appearance (e.g., Cooper et al, 2012; Diehl et al, 2018), goal achievement (e.g., Lower-Hoppe et al, 2021; Snyder et al, 2017), entertainment/stimulation (e.g., Munusturalar et al, 2015; Shapiro et al, 2020). A few studies also investigated communication and marketing practices like information dissemination (e.g., Lee et al, 2020), the use of social media (e.g., Achen, 2015), the internet and word of mouth (e.g., Bilos & Galic, 2016), promotional items (e.g., Ciuffo et al, 2014), advertising and branding (e.g., Mills & Williams, 2016), and the campus recreation facility as an institutional recruitment tool (e.g., Weaver et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…To combat constraints, studies identified participation enablers such as peers (e.g., Webb & Forrester, 2016), the breadth and access to opportunities (e.g., Brunton & St Quinton, 2021;Lower et al, 2015;Snyder et al, 2017;Zuest et al, 2021), financial resources (e.g., Fricke et al, 2018;Wood & Danylchuk, 2015), self efficacy (e.g., Lower-Hoppe et al, 2021) and previous experience (Lyons et al, 2018. Studies also explored the motivational factors of participation such as socialization/peer support, competency/mastery (e.g., Beggs et al, 2014;Carter-Francique, 2011;Deng et al, 2021;Ramos et al, 2018), appearance (e.g., Cooper et al, 2012;Diehl et al, 2018), goal achievement (e.g., Lower-Hoppe et al, 2021;Snyder et al, 2017), entertainment/stimulation (e.g., Munusturalar et al, 2015;Shapiro et al, 2020). A few studies also investigated communication and marketing practices like information dissemination (e.g., Lee et al, 2020), the use of social media (e.g., Achen, 2015), the internet and word of mouth (e.g., Bilos & Galic, 2016), promotional items (e.g., Ciuffo et al, 2014), advertising and branding (e.g., Mills & Williams, 2016), and the campus recreation facility as an institutional recruitment tool (e.g., Weaver et al, 2017).…”
Section: Themesmentioning
confidence: 99%
“…The recreation services indicator, on the other hand, measures the quantity and quality of various sports and leisure activities which comprise tennis and basketball courts, soccer and rugby fields, swimming pools, entertainment centres fitted with pools, and games machines. The need for recreation services has academic benefits for international students [24] and student ID card data can be useful in terms of enabling the effective planning and management of recreation facilities [25]. Finally, intramural sports develop distinct and holistic benefits and physical health and wellness [26].…”
Section: Smart Economymentioning
confidence: 99%